Mezenhimske matične celice - Zupan, Janja (Farmacevtski vestnik, 2017)
Mesenchymal stem cells (MSCs) present a rare and heterogeneous population of multipotent progeni- tors ubiquitously present in different tissues including those of adults. Due to their immunosuppressive capabilities and potential to regenerate various con- nective tissues such as bone, cartilage and skeletal muscles, they possess a massive potential for the treatment of various diseases and injuries of musculoskeletal tissues. Within the musculoskeletal system, most well recognized are those from bone tissue, skeletal muscles and joint membrane. Despite the vast progress in their identification and clinical use, changes within MSCs and/or their microenvironment that could potentially initiate musculoskele- tal diseases, such as osteoporosis, osteoarthritis and sarcopenia, are still poorly understood. Due to this fact, the potential of MSCs in diagnosing these conditions is still largely unexploited. The major barriers preventing the progress in this field are loose d efinition of MSCs, their tissue heterogeneity and lack of specific markers. here we provide an overview of current knowledge on the role of MSCs in musculoskeletal system, their use in regenerative medicine and their potential in diagnosing disorders of this important body system.
Keywords: Diagnostika; imunosupresija; mezenhimske matične celice (MSC); mišično-skeletni sistem; regeneracija